2017
DOI: 10.3727/096504017x14897896412027
|View full text |Cite
|
Sign up to set email alerts
|

LINC00052 Promotes Gastric Cancer Cell Proliferation and Metastasis via Activating the Wnt/β-Catenin Signaling Pathway

Abstract: Gastric cancer (GC) is one of the most common malignant tumors of the digestive system. The etiology of GC is complex, and much more attention should be paid to genetic factors. In this study, we explored the role and function of LINC00052 in GC. We applied qRT-PCR and Northern blot to detect the expression of LINC00052 and found it was highly expressed during GC. We also investigated the effects of LINC00052 on tumor prognosis and progression and found that LINC00052 indicated poor prognosis and tumor progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Previous studies have shown that LINC00052 suppressed the metastasis of HCC cells by upregulating EPB41L3 by means of binding miR-452-5p 9 and regulated NTRK3 expression to facilitated HCC cell metastasis via miR-485-3p and miR-128. 8 In breast cancer, LINC00052 promoted tumor growth by interplay with receptor tyrosine-protein kinase erbB-3 (HER3), 12 in gastric cancer, LINC00052 promoted cell proliferation and metastasis by activating the Wnt-β-catenin signaling pathway. 11 Nevertheless, what LINC00052 work in CRC had not been explored and what are the biological characteristic and mechanism of LINC00052 in CRC?…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that LINC00052 suppressed the metastasis of HCC cells by upregulating EPB41L3 by means of binding miR-452-5p 9 and regulated NTRK3 expression to facilitated HCC cell metastasis via miR-485-3p and miR-128. 8 In breast cancer, LINC00052 promoted tumor growth by interplay with receptor tyrosine-protein kinase erbB-3 (HER3), 12 in gastric cancer, LINC00052 promoted cell proliferation and metastasis by activating the Wnt-β-catenin signaling pathway. 11 Nevertheless, what LINC00052 work in CRC had not been explored and what are the biological characteristic and mechanism of LINC00052 in CRC?…”
Section: Discussionmentioning
confidence: 99%
“…It is well-documented that WNT/β-catenin pathway involves in a wide variety of cellular processes, such as cell growth, cell cycle, differentiation, tumorigenesis and chemoresistance (10,13,26,27). Recent evidence has showed that WNT/β-catenin pathway serves as a good biomolecular target for GC treatment (28).…”
Section: Discussionmentioning
confidence: 99%
“…The function of LINC00052 varies depending on the location of tumors. It acts as a tumor suppressor through inhibiting cell proliferation, invasion and migration in hepatocellular carcinoma (Xiong et al 2016;Yan et al 2018;Zhu et al 2017), whereas it could promote breast cancer growth (Salameh et al 2017) and gastric cell metastasis and proliferation (Shan et al 2017).…”
Section: Discussionmentioning
confidence: 99%